Waist‐hip ratio as a moderator of the effects of hormone therapy on cognitive function in recently menopausal women. (31st December 2021) - James, Taryn T.; Dowling, N. Maritza; Simó, Carola A. Ferrer; Zuelsdorff, Megan; Bouges, Shenikqua; Lambrou, Nickolas H.; Van Hulle, Carol A; Johnson, Adrienne L.; Wyman, Mary F.; Salazar, Hector; Umucu, Emre; Kara, Firat; et al.
Abstract: Background: Research on menopausal hormone therapy (MHT) for the reduction/prevention of cognitive decline or Alzheimer's disease has been inconsistent. The Women's Health Initiative Memory Study (WHIMS) revealed elevated incident cognitive impairment for women starting MHT after age > 65 with oral conjugated equine estrogens (o‐CEE) treatment, especially among women with diabetes. Subsequently, the Cognitive and Affective substudy of the Kronos Early Estrogen Prevention Study (KEEPS‐Cog) found that MHT initiated soon after menopause caused neither cognitive benefit nor harm. Waist‐to‐hip ratio (WHR) is a measure of central adiposity and a surrogate marker for insulin resistance/prediabetes. To explore effects of MHT in insulin‐resistant states, in younger women, we analyzed WHR as a predictor of cognitive response to MHT in KEEPS‐Cog. Methods: KEEPS‐Cog randomized women less than 36‐months postmenopause to oCEE, transdermal 17‐β‐estradiol (tE2) or placebo for 48 months. Cognitive tests, completed at baseline, 18, 36, and 48 months post‐randomization were summarized as factor scores representing four cognitive domains: verbal learning and memory (VLM), auditory attention and working memory (AAWM), visual attention and executive function (VAEF), and speeded language and mental flexibility (SLMF). WHR, measured at screening and months 12, 36, and 48 was modeled as a time‐varying moderator of MHT on cognitive function over time. Education was included as a time‐invariant covariate. Results: WHR decreased throughout the study in both the tE2 and oCEE groups compared to placebo. WHR was also inversely associated with all cognitive parameters at baseline. The inverse relationship of WHR on SLMF was significant at baseline and month 18, but decreased at month 48. The inverse relationship of WHR on VLM increased significantly over time. Models including interaction effects were significant for oCEE x WHR effects at months 18, 36, and 48 on SLMF, indicating better performance in MHT vs placebo arms. No other interaction effects were significant. Conclusions: WHR decreased with MHT, and was consistently associated with VLM through 4 years of MHT. Further, women on oCEE performed better on SLMF tasks at a given WHR. Differences between KEEPS‐Cog and WHIMS findings may be related to the timing of MHT administration, and effects on central adiposity/insulin resistance/prediabetes.